Ethanol Extract of Stylissa carteri Induces Cell Death in Parental and Paclitaxel-Resistant Cervical Cancer Cells - Isna Nisrina Hardani; Fachreza Aryo Damara; Annisa Dewi Nugrahani; Muhammad Hasan Bashari (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To evaluate the cytotoxic effects of ethanol extract from marine sponge Stylissa carteri in both parental and paclitaxel-resistant HeLa cervical cancer cells. Methods: This was an experimental in-vitro study subjected ethanol extract from Stylissa carteri obtained from Pramuka Island, Kepulauan Seribu National Park, Jakarta. Both parental and paclitaxel-resistant HeLa cells were treated with ethanol extract followed by microscopic observation and MTT assay. The IC50 and drug curves were analyzed using four-parametric logistic regression by SigmaPlot for Windows version 12.0 from Systat Software Inc., USA.Results: Ethanol extract from Stylissa carteri triggered cell death-associated morphological changes in parental Hela cells. It demonstrated cytotoxic activities with an IC50 value of 1 ppm. Importantly, this extract also triggered cell death in paclitaxel-resistant HeLa cells. The IC50 of ethanol extract of Stylissa carteri was 4 ppm in paclitaxel-resistant HeLa cells.Conclusions: There is a potential cytotoxic activity of Stylissa carteri that is not only confirmed in parental HeLa cells but also in paclitaxel-resistant HeLa cells.Keywords: Cervical cancer, paclitaxel resistance, HeLa cells, cytotoxicity assay, Stylissa carteri DOI: 10.15850/ijihs.v6n2.1378